Electroweak gauge invariant Higgs multiplets - M. Maniatis (Journal of High Energy Physics)
Abstract We investigate the potential of general Higgs multiplets. We establish the domain of general Higgs multiplets within the context of the adjoint representation. The construction of the most general potential for arbitrary multiplets is achieved using the irreducible, totally symmetric representation of tensor products of doublets. Furthermore, we explore symmetry transformations of the Higgs multiplets, with particular emphasis on CP symmetries.